Strengthening Teacher-Parent Collaboration in Moral Education: A Case Study at Islamic Boarding Schools Al-Izz Sukabumi - Sofa Sari Miladiah; Ade Tutty R. Rosa; Fahrurozi, Fahrurozi; R. Supyan Sauri (CV. Media Digital Publikasi Indonesia, 2026)
The collaboration between teachers and parents in shaping the moral character of students in Islamic boarding schools is crucial yet often overlooked. This study aims to analyze the collaboration between teachers and parents in shaping students' moral character at Islamic boarding schools Al-Izz Sukabumi. This research employs a qualitative case study approach to explore the planning, implementation, and evaluation of teacher-parent collaboration. Data were collected through in-depth interviews, observations, and documentation involving teachers, parents, and school administrators. Thematic analysis was conducted to identify key patterns and challenges in fostering students' moral development. Findings reveal that the collaboration is planned through meetings, home visits, and communication via digital platforms such as WhatsApp groups. The implementation involves joint activities such as parenting workshops and counseling sessions. Evaluation is conducted regularly through meetings and feedback mechanisms. Challenges include parental disengagement due to economic constraints, generational gaps, and limited awareness of their role in moral education. Effective collaboration between teachers and parents enhances students' moral development by providing consistent guidance at home and school. Improved communication and active parental involvement are critical in addressing behavioral challenges. The study suggests strengthening communication channels and developing more inclusive programs to foster parental engagement. Teacher-parent collaboration significantly impacts students' moral character development in Islamic boarding schools. Strengthening communication and parental involvement can enhance the effectiveness of moral education efforts. Further research is recommended to explore similar collaborations in different educational settings.